Innovations in Pharmacotherapy of Diabetes: A Review of Latest Reports - Katarzyna Czechowska; Aleksandra Świerczewska; Piotr Komasara; Julia Nowakowska; Aleksandra Sędek; Lena MERCHEL; Ilona Bednarek; Sylwia Lach; Karol Seweryn Błąd; Kinga Kałuża (Journal of Education, Health and Sport, 2025)
Introduction and purpose